Association of morphological traits with lodging resistance in spring barley under the conditions of the Volga-Vyatka region - I. Yu. Zaytseva; I. N. Shchennikova (Труды по прикладной ботанике, генетике и селекции, 2020)
Background. Lodging has an extremely negative impact on barley yield: grain quality and planting properties are deteriorated, disease incidence increases, and mechanized harvesting becomes difficult, so it is important to find new sources of lodging resistance in barley and use them in crosses and breeding programs to develop non-lodging barley cultivars.Materials and methods. Experimental work was carried out in 2018 and 2019 at Federal Agricultural Science Center of the North-East (FASC North-East), Kirov. Yield structure components and lodging resistance levels were assessed for 29 accessions from the spring barley collection. The study was based on the International COMECON List of Descriptors for the Genus Hordeum L. (subgen. Hordeum) and Methodological Guidelines for the Study and Preservation of the World Collection of Barley and Oats.Results and conclusions. Lodging resistance was observed to have a strong correlation with yield (r = 0.72) and plant height (r = –0.60), and a medium correlation with tillering (r = 0.40) and number of nodal roots at maturation (r = 0.44). No relationship was found between lodging resistance and morphological features of the second lowest internode, which means that selection of non-lodging forms by these criteria will not be effective. Lodging-resistant accessions demonstrated higher yield, tillering, productivity, 1000 grain weight, and a longer and denser ear compared to nonresistant accessions. Accessions combining high yield with lodging resistance and a set of traits promising for breeding were identified: ‘Belgorodsky 100’, ‘Naran’ (k-30892), ‘Kazminsky’ (k-30926), ‘Shchedry’ (k-31046) (Russia); ‘Syabra’ (k-30917), ‘Raider’ (Belarus); ‘Odesssky 115’ (k-29010, Ukraine), ‘Mie’ (k-30379, Estonia), ‘Rodos’ (k-30256, Poland).